Library and information professionals figures in Spain - Delgado-López-Cózar, Emilio; De-la-Moneda-Corrochano, Mercedes (Anuario ThinkEPI, 2008)
A picture is presented of the state of library and information professionals and disciplines in Spain. Statistical data are provided about both the number and type of Spanish libraries and archives as well as practising professionals according to geographic distribution, training and job description. Spanish library and information authorities are identified as well as professional associations and learned societies and conferences held. University education is examined describing existing institutions, degree levels and providing data on student enrollment and teachers.